PENGARUH MODEL DISCOVERY LEARNING DENGAN LKS BERBASIS PENEMUAN TERHADAP HASIL BELAJAR, KETERAMPILAN PROSES SAINS, SERTA MINAT BELAJAR PADA KONSEP GETARAN DAN GELOMBANG DI SMPN 1 KOTA BENGKULU - Inka Novita; Afrizal Mayub; Eko Swistoro (UNIB Press, 2017)
This study aims to to determine the influence of discovery learning model with LKS based on the discovery of learning outcomes and skills of science process, and to describe students' interest in class VIII at SMPN 1 Kota Bengkulu. This type of research includes Quasi Experiment.The sample was obtained using purposive sampling technique that is class VIII.5 as experiment class and class VIII.4 as control class.. Based on the result of data analysis using T-test of two independent samples indicate that there is significant influence of discovery learning model with LKS based on the discovery of the students' learning result because tcount> ttable (8,16> 2,00), science process skill students tcount> ttable (5,9> 2,0), and students' average learning interest of 35.8 in interest categories and student learning interest for very high, high, low and very low categories of 6.06%, 69, 67%, 18.18%, and 6.06%. So it is concluded that there is an influence of using discovery learning model with LKS based on discovery of learning outcomes, science process skills, and student learning interest.